Antenatal Midwifery Care for Mrs. “A” 43 Weeks 3 Days Gestation with Serotinous Pregnancy at the Maternity Clinic Helfylianta Besitang in 2019 - Arnof Yerni; Siti Sundari; Sohiba; Erika Virgisari (Institute of Computer Science (IOCS), 2019)
Gestational age is considered normal if delivery occurs within 37 weeks to 42 weeks of gestation, exceeding this age limit is considered a post-term pregnancy. At a certain level, it can have a negative impact on both the mother and the baby being born, but it can also be fatal. Statistical data shows that the maternal mortality rate in term pregnancies is only 1-2%, while those in late pregnancy reach 5-7%. Objective: To carry out midwifery care for Mrs. A at 43 weeks and 3 days of gestation with serotinus using a 7-step Varney midwifery management approach. The method used is descriptive observation, the location of the case study is at the Maternity Clinic Helfylianta Besitang, the subject of the case study is Mrs. A. Pregnant women with serotinous pregnancy. The time of the case study was on December 3 – 5 2019 and data collection techniques through interviews, on the acceptor Observation physical examination, documentation study, literature study. After 3 days of midwifery care, starting from 3 – 5 December 2014 Mrs. A 21 years old with serotinous pregnancy at the Helfylianta Maternity Clinic, the results of the care obtained were serotinus with a gestation of 43 weeks 3 days with no signs of labor. collaboration with Dr. Obgyn recommending induction of labor. From the results of the case study, it was found that pregnant women with serotinus after 3 days of treatment and the mother still had no signs of labor after collaboration with Dr. Obgyn were recommended induction and delivery at the hospital, the mother was referred